Pengaruh Konsep Diri, Kemandirian Belajar, Kesiapan Belajar, Perhatian Orangtua Dan Fasilitas Belajar Terhadap Hasil Belajar Siswa Kelas Xi IPS Pada Mata Pelajaran Ekonomi di SMA Negeri 2 Batang Anai - Mesi Utami; Rika Verawati; Meri Rahmania (Horizon, 2022)
This study aims to analyze the sampling technique using the Proportional Random Sampling method. The sample in this study was 98 students. The results of self-concept research have a significant effect on learning outcomes. the respective coefficients are 0.188. With the value of tcount tcount 3.193 > ttable 1.66159 This means that if self-concept increases by one unit, then learning outcomes increase by 0.188 in each unit. Independent learning is significant to learning outcomes. The respective coefficients are 0.315. learning readiness has a significant effect on learning outcomes. the respective coefficients are 0.320. Parental attention has a significant effect on learning outcomes. the respective coefficients are 0.437. Learning facilities have a significant effect on learning outcomes. their respective coefficients are 0.208. self-concept, learning independence, learning readiness, parental attention and learning facilities together have a significant effect on learning outcomes. Where obtained the value of Fcount 45.625 > Ftable 2.31 with a significant level of 0.000 < = 0.05. This means that Ha is accepted and H0 is rejected.Keywords: Self-concept, learning independence, learning readiness, parental attention and learning facilities.